Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3892/or.2015.3850
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin exhibits antiproliferative effects on spheres derived from canine mammary carcinoma cells

Abstract: Mammary cancer is the most frequent type of tumor in the female canine. Treatments are mainly limited to surgery and chemotherapy; however, these tumors may develop clinical recurrence, metastasis and chemoresistance. The existence of a subpopulation of cancer cells with stemness features called cancer stem-like cells, may explain in part these characteristics of tumor progression. The statins, potent blockers of cholesterol synthesis, have also shown antitumor effects on cancer mammary cells, changes mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 42 publications
3
29
0
Order By: Relevance
“…A number of studies demonstrated the existence of stem cells in canine and human breast cancer cell lines [83][84][85][86][87][88][89]. The study of Dontu and colleagues demonstrated that the stemness of tumor cells is assessed in vitro by their capability to produce mammospheres [90].…”
Section: Effect Of Melatonin In Epithelial Mesenchymal Transition Marmentioning
confidence: 99%
“…A number of studies demonstrated the existence of stem cells in canine and human breast cancer cell lines [83][84][85][86][87][88][89]. The study of Dontu and colleagues demonstrated that the stemness of tumor cells is assessed in vitro by their capability to produce mammospheres [90].…”
Section: Effect Of Melatonin In Epithelial Mesenchymal Transition Marmentioning
confidence: 99%
“…Previous studies have used this method to analyze the sphere-forming ability of canine mammary CSCs (15,23). This method has also been used to investigate novel therapeutic drugs in humans and canines (14,24). In the present study, it was observed that spheres from canine mammary carcinoma cell lines overexpressed the stem cell markers CD44 and Oct-4, and exhibited chemoresistance to DOX and DDP.…”
Section: Discussionmentioning
confidence: 49%
“…Furthermore, activation of the Wnt/β-catenin, Hedgehog and Notch signaling pathways confers resistance and survival to CSCs in human cancer (13). Similar to what has been observed in human cancer, canine mammary CSCs upregulate stem cell-associated genes (9) and activate the Wnt/β-catenin signaling pathway (14). Canine mammary CSCs are highly tumorigenic, and exhibit multidrug resistance and invasive potential (9,15); therefore, they serve an important role in the treatment resistance, recurrence and metastasis of canine mammary tumors.…”
Section: Introductionmentioning
confidence: 55%
“…The same cells were resistant to radiation doses of 1–5 Gy and exhibited a reduced loss of colony formation ability. Increased resistance to doxorubicin and no response to paclitaxel treatment were also observed by three other groups [27, 31, 35]. Barbieri et al [31] did not observe any reduction in cell viability, even at the highest concentrations (5–10 µM) of the drugs.…”
Section: Functional Characterization Of Canine Mammary Cancer Stem Cellsmentioning
confidence: 60%
“…Human breast CSC have been previously characterized as CD44 + /CD24 −/low [15]. Detection of CD44 + /CD24 −/low cells has also been reported in CMT [27, 30, 35]. A study by Michishita et al [27] demonstrated that 85% of cells were CD44 + /CD24 −/low in spheres derived from a canine mammary adenocarcinoma cell line.…”
Section: Isolation Of Canine Mammary Cancer Stem Cellsmentioning
confidence: 99%